An entry strategy with innovation and differentiation in Brazil and the United States - Fankuchen, Alexander (2014)
With the global rise of credit and debit card usage, acquirers play an increasingly important role within the payments industry by processing these types of payment transactions on behalf of merchants. This study focuses on examining two markets – Brazil and the United States – by providing an overview of the market dynamics, the state of the competitive landscape, and the role and impact of regulations and new technologies. In considering these factors, strategic recommendations are provided for new players interested in enter either market. Further, factors such as existing and future opportunities as well as risks are considered.